A technique grass using a high crude Fibre to maintain the growth performance and improve blood health indicators in beef, central Vietnam - Loi, Bui Van; Thu, Doan Thi Phuong (International Journal of Innovative Research and Scientific Studies, 2025)
Sixteen beef cattle were divided into two groups (Trial 1 - Control, n = 8 beefs and Trial 2 - Experimental, n = 8 beefs) to evaluate the value of lemongrass (Leptocarpus disjunctus Mast.) as feed for cattle in the dry and flood seasons and aiming to develop beef farming, based on the nutritional value for growth maintenance and improve the haematology for health. Growth rate by period was also weighed, and blood samples were collected at 3 months intervals from Vena jugularis for analysis of red blood cell count: haemoglobin (HGB), mean corpuscular volume (MCV), mean corpuscular HGB (MCH), mean corpuscular haemoglobin concentration (MCHC), hematocrit (HCT), white blood cell count (WBC) between two groups are differences, P < 0.001 and differential leukocyte (lymphocytes -LYM), monocytes – MON, and granulocytes-GRA). The amount of all measured indices, hematocrit (HCT), white blood cell count (WBC) and differential white blood cell in the two groups, LYM, MON, and GRA percentages, were not significantly different from the control group and trial (p > 0.05). Therefore, the absolute and percentage values ​​of LYM, MON, and GRA in trial 1 compared to trial 2 (eating a lot of lemon grass) are much better for resisting disease. The blood values ​​of these analytes were in trial 1 (commercial feed and local grass species), giving higher indices.